SEISMIC REFRACTION SURVEY FOR FOUNDATION INVESTIGATION AT AHMADU BELLO UNIVERSITY ZARIA PHASE II, KADUNA STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Ahmadu Bello University Zaria Phase II was investigated for foundation purpose. Four shallow seismic refraction profiles were carried out using the ABEM Terraloc Pro seismograph. Compressional (P) and shear (S) waves were acquired and the time-term technique, which is a combination of linear least squares and delay time analysis to invert the first arrivals for a velocity section and then to tomography section was adopted. These sections were correlated with a borehole report and a good matching was observed. The result shows that the area consists of three subsurface layers; an overburden with average thickness of about 10.5 m and P- and S-wave velocities (velocities) of about 550 m/s and 345 m/s respectively, the weathered basement with an average thickness of 12.5 m and velocities of 950 m/s and 550 m/s respectively, while the fresh basement was found at a depth of about 24 m with velocities of  1250 m/s and 680 m/s respectively. The Concentration Index, Material Index, Poisson’s Ratio, and Stress Ratio were calculated to be in the range of 4.869 – 6.128, -0.032 – 0.312, 0.172 – 0.258, and 0.267 – 0.346 respectively in the study area. The seismic velocity values, engineering consolidation, and strength parameters showed that the subsurface soil/rock at the eastern parts of the study area is characterized by less competent soil/rock quality while the western parts are characterized by more competent soil/rock quality. Hence, the western and northwestern parts are more preferable for the foundation of structures to be erected
Keywords: Seismic refraction, P-and S-waves, geotechnical, near-surface